In vitro factor XIII supplementation increases clot firmness in Rotation Thromboelastometry (ROTEM®) - Theusinger, Oliver M.; Baulig, Werner; Asmis, Lars M.; Seifert, Burkhardt; Spahn, Donat R. (Thrombosis and Haemostasis, 2010)
Factor XIII (F XIII) is an essential parameter for final clot stability. The purpose of this study was to determine the impact of the addition of factor (F)XIII on clot stability as assessed by Rotation Thromboelastometry (ROTEM®). In 90 intensive care patients ROTEM® measurements were performed after in vitro addition of F XIII 0.32 IU, 0.63 IU, 1.25 IU and compared to diluent controls (DC; aqua injectabile) resulting in approximate F XIII concentrations of 150, 300 and 600%. Baseline measurements without any additions were also performed. The following ROTEM® parameters were measured in FIBTEM and EXTEM tests: clotting time (CT), clot formation time (CFT), maximum clot firmness (MCF), maximum lysis (ML), maximum clot elasticity (MCE) and α-angle (αA). Additionally, laboratory values for FXIII, fibrinogen (FBG), platelets and haematocrit were contemporaneously determined. In the perioperative patient population mean FBG concentration was elevated at 5.2 g/l and mean FXIII concentration was low at 62%. The addition of FXIII led to a FBG concentration-dependent increase in MCF both in FIBTEM and EXTEM. Mean increases in MCF (FXIII vs. DC) of approximately 7 mm and 6 mm were observed in FIBTEM and EXTEM, respectively. F XIII addition also led to decreased CFT, increased αA, and reduced ML in FIBTEM and EXTEM. In vitro supplementation of FXIII to supraphysiologic levels increases maximum clot firmness, accelerates clot formation and increases clot stability in EXTEM and FIBTEM as assayed by ROTEM® in perioperative patients with high fibrinogen and low FXIII levels.
Keywords: Thromboelastometry; blood coagulation; haemostasis; thromboelastography; factor XIII